2017
DOI: 10.1371/journal.pone.0184823
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability and minimal detectable change of the Beck Depression Inventory and the Taiwan Geriatric Depression Scale in patients with Parkinson's disease

Abstract: BackgroundThe Beck Depression Inventory II (BDI-II) and the Taiwan Geriatric Depression Scale (TGDS) are self-report scales used for assessing depression in patients with Parkinson’s disease (PD) and geriatric people. The minimal detectable change (MDC) represents the least amount of change that indicates real difference (i.e., beyond random measurement error) for a single subject. Our aim was to investigate the test-retest reliability and MDC of the BDI-II and the TGDS in people with PD.MethodsSeventy patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…The SDC is the smallest threshold of a change score that is beyond random error at a certain confidence level. 32,33 The present research showed small SDC values, they indicated that low differences between consecutive assessments of a single patient are able to announce a real change beyond random error.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The SDC is the smallest threshold of a change score that is beyond random error at a certain confidence level. 32,33 The present research showed small SDC values, they indicated that low differences between consecutive assessments of a single patient are able to announce a real change beyond random error.…”
Section: Discussionsupporting
confidence: 50%
“…Reliability is of central importance in assessment of agreement between measurements in successive sessions. 32 Reliability depends on both ICC and SEM of subjects taking an assessment. The SEM is the amount of error that can be attributed to measurement error, and it is an adequate calculation if one needs a general statistic for describing the accuracy of the score achieved by a randomly chosen subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors (Ertan, Ertan, Kızıltan, & Uyguçgil, 2005;Huang, Hsieh, Wu, & Lu, 2017;Weintraub, Oehlberg, Katz, & Stern, 2006) have attested the reliability and validity of the GDS among patients with Parkinson's Disease. GDS has also been identified as a suitable tool for screening purpose in older adults with different gender, educational level and age (Conradsson, 2013;Chiesi et al, 2017;Dias et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The review also showed that the most commonly used instruments for the diagnosis of SUD or OPD were the International Composite Diagnostic Interview (Robins et al, 1988), the Mini International Neuropsychiatric Interview (Sheehan et al, 1997), and the Structured Clinical Interview of the DSM-IV for Axis I (Lobbestael, Leurgans, & Arntz, 2011), while the instruments used for Brazil 4 2 1 29 36 Chile --5 5 Colombia 1 --5 6 Costa Rica --2 2 Guatemala ---2 2 Jamaica ---1 1 Mexico 2 --14 16 Nicaragua ---1 1 Panama ---1 1 Paraguay ---1 1 Uruguay ---1 1 detections were the Hospital Anxiety and Depression Scale (Zigmond & Snaith, 1983); the Hamilton Depression Scale (Bagby, Ryder, Schuller, & Marshall, 2004), Depression Scales (Huang, Hsieh, Wu, & Lu, 2017), and Beck's Anxiety Index (Magán, Sanz, & García-Vera, 2008). Despite efforts made in Latin America, the results showed that the number of publications in scientific journals on the subject is limited (this is particularly critical when comparing to other developed countries such as the US, Canada, and those in Europe).…”
Section: Stage 2: Review Of Literature On Ddsmentioning
confidence: 99%